Effects of different miracle fruit products on the sensory characteristics of different types of sour foods by descriptive analysis - Choi, Sung Eun; Garza, Jeff (Journal of food science, 2020)
Miracle fruit's potential benefit is encouraging as a powerful antioxidant and sweetness enhancer due to its novel ability to modify sour taste to sweet. However, further studies are needed to evaluate the practicality of different miracle fruit products. Thus, this study aimed to characterize the taste modification effects of different miracle fruit products on different sour foods. For this, 10 trained subjects (80% female, 50% white, Mean ± SE = 27.3 ± 3.9 years old) performed a Quantitative Descriptive Analysis using a Latin Square design with three replications. One session was composed of pre‐ and posttest for miracle fruit administration. Five food samples (green apple, goat cheese, lemonade, plain fat‐free yogurt, and cucumber pickle) and four miracle fruit products (three different brands of miracle fruit pill‐Y, G, M and one powder product‐P) were used and data were analyzed using analysis of variance and principal component analysis. The typical effects of miracle fruit, sweetness increase and sourness suppression were observed for all food samples albeit to different degrees. Y and M pills were most impactful while powder product was least, and goat cheese and yogurt had the most pronounced impact at increasing sweetness. Prior Miracle Fruit administration significantly decreased bitterness and increased creaminess in yogurt. However, it increased off‐flavor in lemonade and pickle. Results suggest that miracle fruit usage for increasing sweetness is effective but the degree of taste‐modifying effect differs according to the types of miracle fruit product and food samples applied. Practical Application This research confirms miracle fruit's unique taste‐modifying abilities and demonstrates a high potential as a sweetness enhancer to benefit human health. The results can be used to optimize miracle fruit's application and can be applied by food industry and health care provider to develop clinical remedies or disease prevention strategies.